The genera Demoulinia Gillies and Potamocloeon Gillies (Ephemeroptera: Baetidae) in Madagascar - Gattolliat, J.-L. (Zootaxa, 2003)
To complete a recent revision of Malagasy Baetidae from still and standing waters, a study of the genera Demoulinia Gillies and Potamocloeon Gillies was undertaken; the latter is reported for the first time from the island. A global revision of the genus is undertaken; the validity of the different species is discussed. A new species of Demoulinia is described herein. Demoulinia assimilis n. sp. is distinguished by the number of segments of the maxillary palp, the shape of the hypopharynx, and the edentate tarsal claws. The systematic position of Demoulinia and Potamocloeon is examined. A redefinition of the Bugilliesia complex is proposed.